EGGS AND EARLY DEVELOPMENTAL STAGES OF HILSA KELEE (CUVIER) - Rao, K Satyanarayana (Indian Journal of Fisheries, 2011)
A type of clupeiod fish eggs 1.005-1.065 mm in diameter with six or seven oil globules recorded in the plankton off Madras coast from February to April and in December in 1967 and in January and March in 1968 have been ascribed to Hilsa kelee (Cuvier) based on the structure of the eggs and larvae hatching from them, the simultaneous occurrence of ripe fish of the species in inshore waters of Madras and coincidence of myotome number of larvae with the number of vertebrae in adult fish.